(untitled) (REVUE DES SCIENCES DE LA SANTE, 2026)
Toxoplasmosis is a parasitic zoonotic disease caused by Toxoplasma gondii. Although generally asymptomatic in immunocompetent individuals, it may lead to severe complications in pregnant women due to the risk of congenital transmission to the fetus, as well as in immunocompromised individuals. In the Democratic Republic of the Congo (DRC), data on the seroprevalence of this infection and the performance of available diagnostic methods remain limited. Therefore, the identification of reliable, accessible, and context-appropriate diagnostic tests is essential for early detection and the prevention of complications associated with this parasitic disease. This cross-sectional analytical study was conducted among women of reproductive age living in the Mateba neighborhood, Limete municipality, Kinshasa. Venous blood samples were collected and analyzed using two serological techniques: immunochromatography and immunofluorescence. The objective was to assess the agreement between these diagnostic methods using the Kappa coefficient and to determine the seroprevalence of toxoplasmosis in the study population. The results showed an overall toxoplasmosis seroprevalence of 67.5%. Agreement analysis revealed a Kappa coefficient of 0.83 for IgG antibodies and 0.85 for IgM antibodies, indicating an almost perfect agreement between immunochromatographic and immunofluorescence techniques in both cases. These findings demonstrate excellent diagnostic concordance between the two serological methods evaluated. Furthermore, 32.5% of the women tested were seronegative for T. gondii, placing them at risk of primary infection during a future pregnancy, with the potential for congenital transmission and adverse fetal outcomes. These results highlight the importance of serological screening and the implementation of appropriate preventive strategies among women of reproductive age in the DRC.